Temperature-induced droplet coalescence in microchannels - Xu, Bin (2012)
This paper reports a technique for temperature-induced merging of droplets in a microchannel. The multiphase system consists of water droplet and oil as the dispersed phase and the carrying continuous phase. A resistive heater provides heating in a rectangular merging chamber. The temperature of the chamber is controlled by the voltage applied to the heater. The merging process of two neighboring droplets was investigated with different applied voltage, flow rate ratio between water and oil and total flowrate. Merging is found to be effective at high flow rate ratio, high temperature, and low total flowrate. The presented technique could be used for merging and mixing in droplet-based lab-on-a-chip platforms.